Therapeutic aphorisms for paranoid personality disorder and paranoid ideation treatment: psychological opposites and complementaries in brief therapy - Bernardo Paoli (Frontiers in Psychology, 2024)
BackgroundIn brief therapy (BT), aphorisms (As) have been considered a privileged element in therapeutic language. With a handful of words, they arouse emotions and different perspectives.Theoretical proposalIn As, a specific structure—the implicit and explicit symmetry of opposites (SoO)—allows a surprise effect, which in turn allows a therapeutic effect. Therefore, a carefully selected SoO (based on psychological complementaries) underlies the desired therapeutic reframing, which can be identified as a core goal of the psychotherapeutic intervention.Research questionIs it possible to identify As with therapeutic value in treating paranoid personality disorder (PPD) and high paranoid ideation (hPI) cases?MethodStarting from an initial collection of 369 original As created on the spot in 2,335 BT sessions, As used during on-line psychotherapy on 55 patients with PPD and/or an hPI measured with the SCL-90-R were identified.ResultsThirty-three As were selected and organised according to effective and ineffective strategies, the target of the BT intervention for PPD and hPI cases.